Alice adventures in wonderland - Carroll, Lewis, 1832-1898.; Zwerger, Lisbeth (Phnom Penh : Footprint International School, 2025)
A little girl falls down a rabbit hole and discovers a world of nonsensical and amusing characters.
Keywords: Fantasy. -- Alice in Wonderland -- Children's literature